Identification and tissue-specific expression of rutin biosynthetic pathway genes in Capparis spinosa elicited with salicylic acid and methyl jasmonate - Kianersi, Farzad; Abdollahi, Mohammad Reza; Mirzaie-asl, Asghar; Dastan, Dara; Rasheed, Faiza (Scientific reports, 2020)
Capparis spinosa is an edible medicinal plant which is considered as an excellent source of rutin. Rutin is a glycoside of the flavonoid quercetin that has been reported to have a beneficial role in controlling various diseases such as hypertension, arteriosclerosis, diabetes, and obesity. In this study, the partial cDNA of four genes involved in the rutin biosynthetic pathway including 4-coumaroyl CoA ligase (4CL), flavonoid 3′-hydroxylase (F3′H), flavonol synthase (FLS) and flavonol-3-O-glucoside L-rhamnosyltransferase (RT) were identified in C.spinosa plants for the first time. The protein sequences of these genes shared high similarity with the same proteins in other plant species. Subsequently, the expression patterns of these genes as well as rutin accumulation in C.spinosa leaves treated with different concentrations of salicylic acid (SA) and methyl jasmonate (MeJA) and also in different tissues of Caper plants treated with 100 mgL −1 SA and 150 μM MeJA were evaluated. The expression of all four genes was clearly up-regulated and rutin contents increased in response to MeJA and SA treatments after 24 h. The highest rutin contents (5.30 mgg −1 DW and 13.27 mgg −1 DW), as well as the highest expression levels of all four genes, were obtained using 100 mgL −1 SA and 150 μM MeJA, respectively. Among the different tissues, the highest rutin content was observed in young leaves treated with 150 μM MeJA, which corresponded to the expression of related genes, especially RT, as a key gene in the rutin biosynthetic pathway. These results suggest that rutin content in various tissues of C. spinosa can be enhanced to a significant extent by MeJA and SA treatments and the gene expression patterns of rutin-biosynthesis-related genes are regulated by these elicitors.